4(7b-8)+8=-3+7(7b+3)

Simple and best practice solution for 4(7b-8)+8=-3+7(7b+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(7b-8)+8=-3+7(7b+3) equation:


Simplifying
4(7b + -8) + 8 = -3 + 7(7b + 3)

Reorder the terms:
4(-8 + 7b) + 8 = -3 + 7(7b + 3)
(-8 * 4 + 7b * 4) + 8 = -3 + 7(7b + 3)
(-32 + 28b) + 8 = -3 + 7(7b + 3)

Reorder the terms:
-32 + 8 + 28b = -3 + 7(7b + 3)

Combine like terms: -32 + 8 = -24
-24 + 28b = -3 + 7(7b + 3)

Reorder the terms:
-24 + 28b = -3 + 7(3 + 7b)
-24 + 28b = -3 + (3 * 7 + 7b * 7)
-24 + 28b = -3 + (21 + 49b)

Combine like terms: -3 + 21 = 18
-24 + 28b = 18 + 49b

Solving
-24 + 28b = 18 + 49b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-49b' to each side of the equation.
-24 + 28b + -49b = 18 + 49b + -49b

Combine like terms: 28b + -49b = -21b
-24 + -21b = 18 + 49b + -49b

Combine like terms: 49b + -49b = 0
-24 + -21b = 18 + 0
-24 + -21b = 18

Add '24' to each side of the equation.
-24 + 24 + -21b = 18 + 24

Combine like terms: -24 + 24 = 0
0 + -21b = 18 + 24
-21b = 18 + 24

Combine like terms: 18 + 24 = 42
-21b = 42

Divide each side by '-21'.
b = -2

Simplifying
b = -2

See similar equations:

| 0.5(x-8)=20 | | .9x=8.1 | | 3x-5+2x=40 | | 1/2h*13=130 | | .1q-.2(3q+4)=-.3(5q+3) | | 9y^2=-11y+14 | | 42=6a | | y=x^2+2kx+n | | -4x-12=x^2 | | 8x^3-512= | | (x-6)(x-5)=(x+7)(x+7) | | 10.6x+95.68=-9.4x+93.94 | | 5(7q+9)+3= | | 36x^2+72x=0 | | y=x^4+3x^2+1 | | 8y=-9x+3 | | 3(i+2)=4i | | 4y-9+y+20=6y+20-4y | | 14x-4x+x+4x=30 | | 1.125=G-4.4 | | 1/4x-5=3/4x-12 | | 5/6x=1/2 | | 12x^3+36x^2=0 | | 2=b*13 | | -2(4)+4y=16 | | -2(2)+4y=16 | | 3(h-3)-2=2(h-5) | | x+x-2x=14 | | -2x+6=-2(3x+7) | | 4.1-Y=2.3 | | -4(2)+5y=8 | | 1.30y=50 |

Equations solver categories